Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How do you start expanding this function $$f(z)= \frac{1}{1+\sqrt{2-z}}$$ into two Taylor expansions about $z=0$?

The best I came up is to let $u=\sqrt{2-z}$ and then expand $f(z)$ as a geometric series.

share|improve this question
    
What do you mean with "two" Taylor expansions? –  Phira Nov 25 '11 at 14:25
1  
Did you consider multiplying numerator and denominator by the conjugate of the denominator? –  Phira Nov 25 '11 at 14:27
    
Your idea cannot work directly because for the geometric series $u$ has to be small, but if $z$ is small, $u$ isn't. –  Phira Nov 25 '11 at 14:27

2 Answers 2

Alternatively, with some algebraic manipulations you get at: $$ f(z) = \frac{1}{1+\sqrt{2-z}} = \frac{1-\sqrt{2-z}}{\left(1+\sqrt{2-z}\right)\left(1-\sqrt{2-z}\right)} = \frac{1-\sqrt{2-z}}{z-1} = \frac{\sqrt{2-z}-1}{1-z} $$ Suppose, you worked out $\sqrt{2-z}-1 = \sum_{n=0}^\infty c_n z^n$, then $$ \frac{\sqrt{2-z}-1}{1-z} = \sum_{n=0}^\infty \left( \sum_{m=0}^n c_m \right) z^n $$

share|improve this answer
    
Thanks this helps.Sorry can't close or upvote the answer. –  citrucel Nov 25 '11 at 19:54

Or, keeping the radical in the denominator, to expand near $z=0$ you should go like this: $$ f(z)= \frac{1}{1+\sqrt{2-z}}=\frac{\displaystyle 1}{\displaystyle(1+\sqrt{2})(1+u)} $$ where $$ u = \frac{\sqrt{2-z}-\sqrt{2}}{1+\sqrt{2}} $$ is near zero. But this will be more work than Sasha's answer.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.